Spinal Cord Injuries Among Genders; Psychological Well- Being - Samir Khan Kabir; Akhlaq Wazir; Naseer Hassan; Ihsan Ullah; Raza Hassan; Anwar Ul Haque Kiani (Gandhara University, 2021)
OBJECTIVES: The aim of this study was to analyse the psychological wellbeing among gender suffering from spinal cord injury (SCI). METHODOLOGY: This was a comparative study. It was conducted from January-March 2020 in Hayatabad Medical Complex (HMC), Peshawar. This study compares the psychological well being in terms of their stress, anxiety, and depression. A questionnaire DASS-42 was used to collect the data from both genders. The inclusion criteria comprise of patients who came for the treatment of their spinal cord injury to the orthopaedic department. Those patients having severe physical and comorbid psychiatric illness were excluded. The data was collected and analysed on SPSS 26. RESULTS: The total sample of 127 in which male were 83 and female were 44. The results were significant according to stress, anxiety, and depression. The level of stress was more in male patients,whereas anxiety results were insignificant among gender and depression were high in females respectively. CONCLUSION: Our results revealed, SCI patients have a high risk of anxiety or depression in among male and female. This information could help physicians understand the long-term risk of new-onset anxiety or depression in SCI patients .